Decellularized bovine meniscus in morphological assessment prior to bioscaffold preparation - Norzarini, A.; Azhim, Azran; Ushida, T. (2015)
Decellularization is a process of tissue treatment targeting cell removal. Sonication system was developed in order to decellularize meniscus tissues. The samples were sonicated in 0.1% sodium dodecyl sulphate (SDS) for 10 hours and at 40 kHz ultrasound frequency. All the samples were structurally examined using van Gieson, Picrosirius red, Safranin-O/Fast green staining, and scanning electron microscopic (SEM) observation. Histological analysis of sonication treated-samples by van Gieson staining demonstrated complete nuclei removal compared to the control samples. The Picrosirius red and Safranin-O/Fast green staining indicate the preservation of collagen and glycosaminoglycans (GAGs) structure, respectively. In addition, the morphological observation by SEM shows the availability of micropores on the surface of decellularized sample. Consequently, the sonication decellularization treatment did not affect extracellular matrix (ECM) properties, while forming micropores on the surface of meniscus tissues. This made it possible to proceed in other fulfillment of bioscaffold preparation.